Expansion material and preparation method and application thereof
By providing a new type of expansion material including an expansion core, a clad layer and an isolation layer, the existing sandproof filter device has solved the problem of high cost, complex processing and inability to support formation sand, and achieved sandproof with high permeability and compressive strength The effect reduces construction costs and simplifies the process.
Patent Information
- Application Number
- CN202210524621.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-13
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-05-13
AI Technical Summary
The existing sandproof filtration device is costly, complex in processing technology, easy to damage, and difficult to salvage. It cannot expand to the formation deficit zone and perforated channel in the oil well completed perforation, and cannot effectively support the formation sand.
A novel expansion material is provided that includes an expanded core, a clad layer and an isolation layer in the direction from the center to the surface, and the expansion core is transformed into an expanded core under high temperature conditions. The preparation method of the material includes pulverizing and sieving to obtain an expanded core, mixing resin and curing agent to produce a coating material, applying it to the surface of the expanded core, and covering it with a spacer.
The expanded material has higher permeability and compressive strength, which can effectively support the rock wall of the perforated channel and prevent rock structure damage and sand migration. Its processing technology is simple and low cost. It is suitable for oil and gas mining, without complex construction sets, and can be refilled and used repeatedly.
Smart Images

Figure CN117089335B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sand control and completion of oil and gas wells, and in particular to an expansion material and a preparation method and application thereof. Background Art
[0002] Sand production in oil and gas wells refers to the process or phenomenon in which, during the production process of an oil or gas well, the rock structure of the strata near the bottom of the well changes due to various comprehensive factors such as geological conditions, mining methods, and operational measures, resulting in discrete sand or detached sand from the formation being carried into the wellbore or the ground by the formation production fluid, thereby causing a series of adverse effects on the normal production of the oil and gas well.
[0003] The main way to solve the problem of sand production in oil and gas wells is to use sand control technology to prevent the sand produced by the formation from entering the wellbore or to artificially strengthen the consolidation degree of the nearby formation rocks to control the formation sand production. The existing sand control technologies are mainly divided into two categories: mechanical sand control and chemical sand control. Specifically, they can be divided into screen sand control technology, gravel filling sand control technology, fracturing sand control technology, artificial well wall sand control technology, chemical sand consolidation technology, etc. These sand control technologies are suitable for different underground conditions and have their own advantages and disadvantages.
[0004] In order to better solve the problem of sand production in oil wells, some new sand control technologies have emerged in recent years. CN102224321A discloses a shape memory polyurethane foam for underground sand control filter device. The underground sand control filter device can be compressed under the condition of being lower than its glass transition temperature by using this shape memory polyurethane foam. After the sand control filter device is lowered into the oil well, it is heated to a temperature higher than its glass transition temperature, so that it expands from the compressed state to the expanded state, and conforms to the wellbore structure, thereby preventing the formation from sand production. Indoor experimental studies have shown that shape memory polyurethane foam has expandability and porous filtering properties, and is an excellent sand control material. The sand control filter device processed using this material was put into field application in 2010. However, this sand control filter device has not been widely promoted and applied in mines so far, mainly because it still has some shortcomings that are difficult to overcome.
[0005] The main problems of the sand filter device are as follows: (1) the amount of shape memory polyurethane foam used is large and the processing technology of the sand filter device is complicated, resulting in a very high cost of the sand filter device, which is much higher than the existing sand control technology; (2) when the sand filter device is lowered into the wellbore, the friction between the sand filter device and the wellbore wall can easily cause damage to the shape memory polyurethane foam wrapping layer on the outer layer of the sand filter device; (3) once the sand filter device fails, it is difficult to salvage it; (4) for oil wells completed by perforation, the sand filter device is used, and its shape memory polyurethane foam cannot expand into the formation deficit zone and the perforation channel, and cannot support the formation sand. The migration of sand particles causes the sand filter device to be blocked and eroded. Summary of the invention
[0006] The purpose of the present invention is to overcome the above technical problems existing in the prior art and provide an expansion material and a preparation method and application thereof. The expansion material has a higher permeability and has little effect on the oil well production; it has a higher compressive strength and plays a better supporting role on the rock wall of the perforation channel to prevent the structural damage of the rock and the migration of rock skeleton sand. There are no special requirements for the shape of the expansion material and no strict requirements for its expansion direction. It is processed into granules by a crusher or a cutter, and the processing technology is simple and the production cost is low.
[0007] In order to achieve the above object, the present invention provides an expansion material in a first aspect, characterized in that, along the direction from the center to the surface, the expansion material comprises an expansion core, an adhesive coating layer and an isolation layer in sequence;
[0008] Under high temperature conditions, the expanded core is transformed into an expanded state core.
[0009] A second aspect of the present invention provides a method for preparing the above-mentioned expansion material, characterized in that the method comprises the following steps:
[0010] (1) crushing and screening the expanded raw material to obtain an expanded kernel;
[0011] (2) mixing the components in the adhesive coating composition with a solvent to obtain a coating material;
[0012] (3) applying the coating material to the surface of the expanded inner core to obtain a semi-finished material;
[0013] (4) The semi-finished material is coated with an insulating material to obtain an expanded material.
[0014] A third aspect of the present invention provides an application of the above-mentioned expansion material in the field of oil and gas production.
[0015] Through the above technical solution, the expansion material and the preparation method and application thereof provided by the present invention achieve the following beneficial effects:
[0016] The expansion material has a higher permeability and has little effect on the oil well production. It has a higher compressive strength and plays a good supporting role on the rock wall of the perforation channel to prevent the rock structure from being damaged and the rock skeleton sand from moving. There are no special requirements for the shape of the expansion material, and there are no strict requirements for its expansion direction. It is processed into particles by a crusher or a cutter, with a simple processing technology and low production cost.
[0017] The expansion material provided by the present invention is applied to the field of oil and gas production. There is no need to lower the screen pipe, the construction is simple, there is no need to fill resin sand, and there is no need for a complex construction vehicle group. The construction process is saved, and the sand control material is saved, which can greatly reduce the cost of sand control measures. After the construction is completed, no pipe column is left in the wellbore, and the full diameter of the wellbore is maintained, which is convenient for production testing and later well repair operations. After the sand control fails, no special treatment is required, and the expansion particles can be repeatedly filled for secondary sand control operations. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is a schematic diagram of the structure of the expansion material;
[0019] Figure 2 It is a schematic diagram of the expansion material filling the perforation channel without expansion;
[0020] Figure 3 A schematic diagram of the expansion material filling the perforation channel after expansion;
[0021] Figure 4 Schematic diagram of the device for measuring the average pore size.
[0022] Description of Reference Numerals
[0023] 1-expanding core, 2-bonding layer, 3-isolation layer, 4-injection pump, 5-formation sand, 6-expanding material in expanded state, 7-beaker, 8-core holder. DETAILED DESCRIPTION
[0024] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0025] In order to achieve the above object, the first aspect of the present invention provides an expansion material, characterized in that, along the direction from the center to the surface, the expansion material comprises an expansion core, an adhesive coating layer and an isolation layer in sequence;
[0026] Under high temperature conditions, the expanded core is transformed into an expanded state core.
[0027] According to the present invention, the expansion core is selected from a thermosensitive shape memory polymer.
[0028] According to the present invention, the temperature-sensitive shape memory polymer is selected from at least one of temperature-sensitive polyurethane, temperature-sensitive epoxy resin, temperature-sensitive polycarbonate, temperature-sensitive styrene-butadiene copolymer, temperature-sensitive styrene-butyl acrylate and temperature-sensitive ethylene-vinyl acetate copolymer, preferably temperature-sensitive polyurethane.
[0029] Furthermore, the temperature-sensitive shape memory polymer is selected from temperature-sensitive polyurethane.
[0030] Furthermore, the temperature-sensitive polyurethane comprises structural units provided by isocyanate and structural units provided by polycarbonate polyol.
[0031] In the present invention, there is no particular limitation on the content of the structural units provided by isocyanate and the structural units provided by polycarbonate polyol in the temperature-sensitive polyurethane, as long as the expanded core made of the temperature-sensitive polyurethane can be transformed into an expanded core under high temperature conditions.
[0032] According to the present invention, the particle size of the expanded inner core is 2-6 mm.
[0033] Furthermore, the particle size of the expanded inner core is 3-5 mm.
[0034] According to the present invention, the high temperature condition is 40-120°C.
[0035] Furthermore, the high temperature condition is 60-80°C.
[0036] According to the present invention, the pore size of the expanded inner core is 0.05-0.35 mm.
[0037] Furthermore, the pore size of the expanded inner core is 0.1-0.25 mm.
[0038] According to the present invention, the permeability of the expanded inner core is 1-200D.
[0039] Furthermore, the permeability of the expanded inner core is 10-100D.
[0040] According to the present invention, the compressive strength of the expanded material in the expanded state is 0.5-10 MPa.
[0041] Furthermore, the compressive strength of the expanded material in the expanded state is 2-5 MPa.
[0042] According to the present invention, the adhesive coating is made from an adhesive coating composition comprising a resin and a curing agent.
[0043] Furthermore, the weight ratio of the resin to the curing agent is 1:1-10.
[0044] In the present invention, the ratio of the resin to the curing agent is within the above range, and the prepared adhesive coating material can maintain a reasonable curing speed and curing strength. By further adjusting the size of the expansion core, the thickness of the adhesive coating and the thickness of the isolation layer, the expansion core of the prepared expansion material expands while the isolation layer is removed, and is accompanied by the curing of the adhesive coating, so that the fully expanded expansion material maintains good mechanical properties and better permeability.
[0045] According to the present invention, the resin is selected from at least one of phenolic resin, epoxy resin, furan resin and unsaturated resin.
[0046] Furthermore, the resin is selected from epoxy resin.
[0047] According to the present invention, the viscosity of the resin at 25° C. is 15-1500 mPa·S.
[0048] The resin raw material used in the present invention is pure resin or a mixture of resin and other components. The solid content of the resin raw material is not particularly limited, as long as the solid content of the resin raw material meets the requirements, for example, the solid content of the resin raw material is 40-100%.
[0049] According to the present invention, the curing agent is selected from at least one of oligomer polyamide 650, triethylenetetramine, ethylenediamine, diethylaminopropylamine, triethylenetetramine, phenalkamine and phenolic resin NL curing agent.
[0050] Furthermore, the curing agent is selected from oligomer polyamide 650.
[0051] According to the present invention, the thickness of the adhesive coating is 30-100 μm.
[0052] In the present invention, the thickness of the adhesive coating is within the above range, which can maintain sufficient bonding strength and avoid blocking the pore size of the expanded core.
[0053] Furthermore, the thickness of the adhesive coating is 50-80 μm.
[0054] According to the present invention, the curing time of the adhesive layer is T1, and the time for the expanded core to transform into the expanded state core is T2, wherein T2 <T1。
[0055] Further, T1-T2=1-6h.
[0056] According to the present invention, the isolation layer is selected from inorganic salts and / or water-soluble polymers.
[0057] Furthermore, the isolation layer is selected from at least one of hydroxypropyl methylcellulose ether, KCl inorganic salt particles, aqueous wax and polyphosphate.
[0058] Furthermore, the isolation layer is selected from hydroxypropyl methylcellulose ether.
[0059] According to the present invention, the thickness of the isolation layer is 50-300 μm.
[0060] In the present invention, the thickness of the isolation layer is within the above range and has a reasonable dissolution rate, ensuring that the isolation layer dissolves before the adhesive layer solidifies.
[0061] Furthermore, the thickness of the isolation layer is 100-200 μm.
[0062] According to the present invention, the ratio of the thickness of the isolation layer to the thickness of the adhesive layer is 1:0.2-1.2.
[0063] In the present invention, the thickness of the isolation layer and the thickness of the adhesive layer are within the above range, which can maintain a reasonable relationship between the dissolution of the isolation layer and the solidification of the adhesive layer, so that the expanded core can be bonded and agglomerated, and can be dissolved before the adhesive layer solidifies.
[0064] Furthermore, the ratio of the thickness of the isolation layer to the thickness of the adhesive layer is 1:0.3-0.8.
[0065] A second aspect of the present invention provides a method for preparing the above-mentioned expansion material, characterized in that the method comprises the following steps:
[0066] (1) crushing and screening the expanded raw material to obtain an expanded kernel;
[0067] (2) mixing the components in the adhesive coating composition with a solvent to obtain a coating material;
[0068] (3) applying the coating material to the surface of the expanded inner core to obtain a semi-finished material;
[0069] (4) The semi-finished material is coated with an insulating material to obtain an expanded material.
[0070] According to the present invention, the viscosity of the coating material is 100-500 mPa·S.
[0071] In the present invention, the viscosity of the coating material is within the above range, which facilitates the coating material to be evenly coated on the surface of the expansion core and prevents the coating material from penetrating into the pores of the expansion core.
[0072] Furthermore, the viscosity of the coating material is 200-300 mPa·S.
[0073] According to the present invention, the amount of the coating material used is such that the thickness of the adhesive layer in the expansion material is 30-100 μm.
[0074] Furthermore, the amount of the coating material used is such that the thickness of the adhesive layer in the expansion material is 50-80 μm.
[0075] According to the present invention, the amount of the isolation material is such that the thickness of the isolation layer in the expansion material is 50-300 μm.
[0076] Furthermore, the amount of the isolation material is such that the thickness of the isolation layer in the expansion material is 100-200 μm.
[0077] According to the present invention, the solvent is selected from any one of ethanol, ethylene glycol monobutyl ether, ethyl acetate, tetrahydrofuran, chloroform and acetone.
[0078] Furthermore, the solvent is selected from ethanol.
[0079] According to the present invention, the coating time is 1-30 minutes.
[0080] Furthermore, the coating time is 5-10 minutes.
[0081] In the present invention, there is no particular limitation on the coating method. For example, coating is completed in a container, specifically: first, the coating material is evenly brushed on the inner wall of the container, and then a certain amount of expanded kernels are added to the container, and the coating is carried out under stirring conditions at a certain speed. The coating time can be selected from any value between 1-30 minutes to obtain a semi-finished material. The stirring speed is not particularly limited here, for example, it can be selected from any value between 30-120 revolutions per minute.
[0082] According to the present invention, the coating time is 1-30 minutes.
[0083] Furthermore, the coating time is 5-10 minutes.
[0084] In the present invention, there is no particular limitation on the coating method. For example, the coating is continued in the above-mentioned container after coating, specifically, adding the isolation material to the container storing the above-mentioned semi-finished material, and coating is carried out under stirring conditions at a certain speed. The coating time can be selected from any value between 1-30 minutes. The stirring speed is not particularly limited here, for example, it can be selected from any value between 30-120 revolutions per minute.
[0085] A third aspect of the present invention provides an application of the above-mentioned expansion material in the field of oil and gas production.
[0086] When the above-mentioned expansion material is used in the field of oil and gas extraction, a filling pipe column is lowered into the oil well, and the well is washed with clean water to flush the sand. Hydroxypropyl guar gum is used to prepare the sand-carrying fluid. The viscosity of the sand-carrying fluid is not particularly limited here, for example, 10-20mPa·S can be selected. Based on the total volume of the sand-carrying fluid, the amount of expansion material added is 10%-60% (the amount of expansion material used here is measured by volume). The expansion material is prepared on site, and the sand-carrying fluid is injected into the formation using a pump truck. The expansion material will be filled into the perforation channel (such as Figure 2 ).
[0087] Use sand-carrying fluid to fill the wellbore with quartz sand to completely cover the entire perforation section to prevent the expansion material from spitting back from the perforation channel during the expansion process. Inject the activator, and after the expansion material is fully expanded, an integral sand control plug is formed in the perforation channel (such as Figure 3 ). Sand flushing and well washing, flushing the quartz sand filled in the wellbore, the construction is completed and put into production.
[0088] In the present invention, there is no particular limitation on the activator, as long as it can promote the transformation of the expansion core into the expansion state core. The activator can be a mixed solution of sodium nitrite and ammonium chloride in a ratio of 1:1 (concentration of 35wt%), which undergoes a chemical reaction in the well to generate heat, increase the downhole temperature, and expand the expansion material; hot water can also be used as an activator to expand the expansion material.
[0089] In the following examples, unless otherwise specified, all raw materials used can be obtained from commercial channels.
[0090] (1) Expansion material: purchased from Baker Hughes Company, brand name GeoFORM, the high temperature condition for causing the expansion of the expansion material is 60°C.
[0091] (2) Resin raw materials: bisphenol A epoxy resin, purchased from Balin Petrochemical, brand E44, viscosity 640 mPa·s, solid content 100%; thermosetting phenolic resin, purchased from Shandong Jinan Baichuan Chemical Co., Ltd., brand 2127, viscosity 320 mPa·s, solid content 75%.
[0092] (3) Curing agent: oligomer polyamide 650, purchased from Bahrain Petrochemical, brand 650; phenolic resin NL curing agent, purchased from Shandong Jinan Baichuan Chemical Co., Ltd., brand NL.
[0093] (4) Isolation material: Hydroxypropyl methylcellulose ether, purchased from Shandong Zhongrun Haihua Chemical Technology Co., Ltd., brand HPMC, molecular weight 100,000.
[0094] The following is the test method of the performance parameters involved in the present invention:
[0095] (1) Permeability: SY / T 5276-2000 “Test methods for flexural strength, compressive strength and permeability of artificial cores for chemical sand control”.
[0096] (2) Compressive strength: SY / T 5276-2000 “Test methods for flexural strength, compressive strength and permeability of artificial cores for chemical sand control”.
[0097] (3) Average pore size: One side of the core holder is filled with expansion material in an expanded state, and the other side is filled with formation sand with a particle size of 0.05-0.85 mm (such as Figure 4 As shown). Use an injection pump to inject clean water from the side containing formation sand into the core holder at a flow rate of 0.5L / min for 4 hours. Under the action of the water flow, part of the formation sand passes through the expansion material in the expanded state and falls into the beaker to obtain a sand sample. The average particle size of the sand sample is the average pore size of the expansion material in the expanded state.
[0098] (4) Test method for curing time T1 of the adhesive coating: Place the expansion material in a glass tube, seal both ends with metal mesh, place in a 70°C water bath, take out after 10 min intervals, open the metal mesh, stir the material with a glass rod, and observe whether the expansion material is bonded and cured. If the material does not disperse when the glass rod stirs the material, this is the curing time T1 of the adhesive coating.
[0099] (5) Test method for the time T2 when the expanded core is transformed into the expanded state core: put the expandable material into a glass tube, seal both ends with metal mesh, put it into a 70°C water bath, take it out after 5 minutes, open the metal mesh, and the time corresponding to the state of the expanded core being fully expanded is T2.
[0100] Example 1
[0101] (1) crushing and sieving the expanded raw material to obtain an expanded kernel with a particle size of 3 mm;
[0102] (2) 10 parts by weight of bisphenol A epoxy resin and 10 parts by weight of oligomer polyamide 650 were uniformly mixed, and then diluted with ethanol to 200 mPa·S to prepare a coating material;
[0103] (3) using a brush, evenly brush the coating material prepared in step (2) on the inner wall of a cylinder with a barrel diameter of 50 cm and a barrel height of 40 cm, pour 100 parts by weight of the expanded core prepared in step (1) into the cylinder, and stir at a stirring rate of 60 rpm for 10 min to evenly coat the coating material on the surface of the expanded core to obtain a semi-finished material;
[0104] (4) Add 2 parts by weight of hydroxypropyl methylcellulose (HPMC) powder to the semi-finished material obtained in step (3), and continue stirring for 5 minutes at a stirring rate of 60 rpm to uniformly coat the surface of the semi-finished material with the HPMC powder to obtain an expandable material.
[0105] The thickness of the adhesive layer is 60 μm, and the thickness of the isolation layer is 100 μm.
[0106] Take 5g of expansion material and put it into a φ25mm glass tube. Connect the two ends of the glass tube to the hot water inlet and the hot water outlet respectively. Pass 70℃ hot water into the glass tube at a flow rate of 0.5L / min to transform the expansion core into the expanded state core.
[0107] The experiment measured that the expansion material in the expanded state has a permeability of 92D, a compressive strength of 4.6MPa, and an average pore size of 0.15mm. The curing time T1 of the adhesive coating is 4h, and the time T2 for the expansion core to transform into the expansion state core is 0.25h.
[0108] Example 2
[0109] (1) crushing and sieving the expanded raw material to obtain an expanded kernel with a particle size of 5 mm;
[0110] (2) 20 parts by weight of a thermosetting phenolic resin and 2 parts by weight of a phenolic resin NL curing agent were uniformly mixed, and then diluted with alcohol to 200 mPa·S to prepare a coating material;
[0111] (3) using a brush, evenly brush the coating material prepared in step (2) on the inner wall of a cylinder with a barrel diameter of 50 cm and a barrel height of 40 cm, pour 100 parts by weight of the expanded core prepared in step (1) into the cylinder, and stir at a stirring rate of 60 rpm for 10 min to evenly coat the coating material on the surface of the expanded core to obtain a semi-finished material;
[0112] (4) Add 20 parts by weight of KCl inorganic salt particles to the semi-finished material obtained in step (3), and continue stirring for 5 minutes at a stirring rate of 60 rpm to uniformly coat the surface of the semi-finished material with HPMC powder to obtain an expanded material.
[0113] The thickness of the adhesive layer is 60 μm, and the thickness of the isolation layer is 200 μm.
[0114] Take 5g of expansion material and put it into a φ25mm glass tube. Connect the two ends of the glass tube to the hot water inlet and the hot water outlet respectively. Pass 70℃ hot water into the glass tube at a flow rate of 0.5L / min to transform the expansion core into the expanded state core.
[0115] The experiment measured that the expansion material in the expanded state has a permeability of 80D, a compressive strength of 3.5MPa, and an average pore size of 0.2mm. The curing time T1 of the adhesive coating is 2.5h, and the time T2 for the expansion core to transform into the expansion state core is 0.25h.
[0116] Example 3
[0117] (1) crushing and sieving the expanded raw material to obtain an expanded kernel with a particle size of 3 mm;
[0118] (2) 10 parts by weight of bisphenol A epoxy resin and 10 parts by weight of oligomer polyamide 650 were uniformly mixed, and then diluted with alcohol to 200 mPa·S to prepare a coating material;
[0119] (3) using a brush, evenly brush the coating material prepared in step (2) on the inner wall of a cylinder with a barrel diameter of 50 cm and a barrel height of 40 cm, pour 40 parts by weight of the expanded core prepared in step (1) into the cylinder, and stir at a stirring rate of 60 rpm for 10 min to evenly coat the coating material on the surface of the expanded core to obtain a semi-finished material;
[0120] (4) Add 2 parts by weight of hydroxypropyl methylcellulose (HPMC) powder to the semi-finished material obtained in step (3), and continue stirring for 5 minutes at a stirring rate of 60 rpm to uniformly coat the surface of the semi-finished material with the HPMC powder to obtain an expandable material.
[0121] The thickness of the adhesive layer is 200 μm, and the thickness of the isolation layer is 98 μm.
[0122] Take 5g of expansion material and put it into a φ25mm glass tube. Connect the two ends of the glass tube to the hot water inlet and the hot water outlet respectively. Pass 70℃ hot water into the glass tube at a flow rate of 0.5L / min to transform the expansion core into the expanded state core.
[0123] The experiment measured that the expansion material in the expanded state has a permeability of 1.6D, a compressive strength of 8.3MPa, and an average pore size of 0.05mm. The curing time T1 of the adhesive coating is 5.5h, and the time T2 for the expansion core to transform into the expansion state core is 0.25h.
[0124] Example 4
[0125] (1) crushing and sieving the expanded raw material to obtain an expanded kernel with a particle size of 3 mm;
[0126] (2) 10 parts by weight of bisphenol A epoxy resin and 10 parts by weight of oligomer polyamide 650 were uniformly mixed, and then diluted with alcohol to 50 mPa·S to prepare a coating material;
[0127] (3) using a brush, evenly brush the coating material prepared in step (2) on the inner wall of a cylinder with a barrel diameter of 50 cm and a barrel height of 40 cm, pour 100 parts by weight of the expanded core prepared in step (1) into the cylinder, and stir at a stirring rate of 60 rpm for 10 min to evenly coat the coating material on the surface of the expanded core to obtain a semi-finished material;
[0128] (4) Add 2 parts by weight of hydroxypropyl methylcellulose (HPMC) powder to the semi-finished material obtained in step (3), and continue stirring for 5 minutes at a stirring rate of 60 rpm to uniformly coat the surface of the semi-finished material with the HPMC powder to obtain an expandable material.
[0129] The thickness of the adhesive layer is 20 μm, and the thickness of the isolation layer is 100 μm.
[0130] Take 5g of expansion material and put it into a φ25mm glass tube. Connect the two ends of the glass tube to the hot water inlet and the hot water outlet respectively. Pass 70℃ hot water into the glass tube at a flow rate of 0.5L / min to transform the expansion core into the expanded state core.
[0131] The experiment measured that the expansion material in the expanded state has a permeability of 11D, a compressive strength of 0.8MPa, and an average pore size of 0.1mm. The curing time T1 of the adhesive coating is 6h, and the time T2 for the expansion core to transform into the expansion state core is 0.25h.
[0132] Example 5
[0133] (1) crushing and sieving the expanded raw material to obtain an expanded kernel with a particle size of 3 mm;
[0134] (2) 10 parts by weight of bisphenol A epoxy resin and 0.5 parts by weight of oligomer polyamide 650 were uniformly mixed, and then diluted with ethanol to 200 mPa·S to prepare a coating material;
[0135] (3) using a brush, evenly brush the coating material prepared in step (2) on the inner wall of a cylinder with a barrel diameter of 50 cm and a barrel height of 40 cm, pour 100 parts by weight of the expanded core prepared in step (1) into the cylinder, and stir at a stirring rate of 60 rpm for 10 min to evenly coat the coating material on the surface of the expanded core to obtain a semi-finished material;
[0136] (4) Add 2 parts by weight of hydroxypropyl methylcellulose (HPMC) powder to the semi-finished material obtained in step (3), and continue stirring for 5 minutes at a stirring rate of 60 rpm to uniformly coat the surface of the semi-finished material with the HPMC powder to obtain an expandable material.
[0137] The thickness of the adhesive layer is 35 μm, and the thickness of the isolation layer is 102 μm.
[0138] Take 5g of expansion material and put it into a φ25mm glass tube. Connect the two ends of the glass tube to the hot water inlet and the hot water outlet respectively. Pass 70℃ hot water into the glass tube at a flow rate of 0.5L / min to transform the expansion core into the expanded state core.
[0139] The experiment measured that the expansion material in the expanded state has a permeability of 35D, a compressive strength of 0.4MPa, and an average pore size of 0.15mm. The curing time T1 of the adhesive coating is 5.5h, and the time T2 for the expansion core to transform into the expansion state core is 0.25h.
[0140] Comparative Example 1
[0141] The isolation layer is omitted, and other performance parameters of the material are the same as those in Example 1.
[0142] The expansion material is added to the sand-carrying fluid. The dispersion of the expansion material in the sand-carrying fluid is very poor. During the construction process, the expansion material is blocked at the wellbore or the entrance of the perforation hole, affecting the pumping construction safety and filling effect of the expansion particles. The curing time T1 of the adhesive layer is 3.83h, and the time T2 for the expansion core to transform into the expansion state core is 0.25h.
[0143] Comparative Example 2
[0144] The adhesive coating was omitted, and other conditions were the same as those in Example 1.
[0145] Take 5g of expansion material and put it into a φ25mm glass tube. Connect the two ends of the glass tube to the hot water inlet and the hot water outlet respectively. Pass 70℃ hot water into the glass tube at a flow rate of 0.5L / min to transform the expansion core into the expanded state core.
[0146] The experiment measured that the permeability of the expansion material in the expanded state is 153D. Since the expansion material in the expanded state is in a loose state, its strength can be ignored, and the average pore size is 0.2mm, which cannot meet the use requirements.
[0147] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An expansion material, characterized in that: Along the direction from the center to the surface, the expansion material comprises an expansion core, an adhesive coating layer and an isolation layer in sequence; Under high temperature conditions, the expanded core is transformed into an expanded state core; The expansion core is a temperature-sensitive shape memory polymer, selected from at least one of temperature-sensitive polyurethane, temperature-sensitive epoxy resin, temperature-sensitive polycarbonate, temperature-sensitive styrene-butadiene copolymer, temperature-sensitive styrene-butyl acrylate and temperature-sensitive ethylene-vinyl acetate copolymer, and the particle size of the expansion core is 2-6 mm; The adhesive coating is made of an adhesive coating composition comprising a resin and a curing agent, the weight ratio of the resin to the curing agent is 1-10:1, the resin is selected from at least one of phenolic resin, epoxy resin, furan resin and unsaturated resin, and the thickness of the adhesive coating is 30-100 μm; The isolation layer is selected from at least one of hydroxypropyl methylcellulose ether, KCl inorganic salt particles, aqueous wax and polyphosphate, and the thickness of the isolation layer is 50-300 μm; The pore size of the expanded inner core is 0.05-0.35 mm.
2. The expansion material according to claim 1, wherein The expansion core is temperature-sensitive polyurethane.
3. The expansion material according to claim 2, wherein The temperature-sensitive polyurethane comprises structural units provided by isocyanate and structural units provided by polycarbonate polyol.
4. The expansion material according to claim 1, wherein The particle size of the expanded core is 3-5 mm.
5. The expansion material according to claim 1, wherein The high temperature condition is 40-120°C.
6. The expansion material according to claim 5, wherein The high temperature condition is 60-80°C.
7. The expansion material according to claim 1, wherein The pore size of the expanded inner core is 0.1-0.25 mm.
8. The expansion material according to claim 1, wherein The permeability of the expanded inner core is 1-200D.
9. The expansion material according to claim 8, wherein The permeability of the expanded inner core is 10-100D.
10. The expansion material according to claim 1, wherein The compressive strength of the expanded material in the expanded state is 0.5-10 MPa.
11. The expansion material according to claim 10, wherein The compressive strength of the expanded material in the expanded state is 2-5 MPa.
12. The expansion material according to claim 1, wherein The resin is epoxy resin.
13. The expansion material according to claim 1, wherein The viscosity of the resin at 25° C. is 15-1500 mPa·S.
14. The expansion material according to claim 1, wherein The curing agent is selected from at least one of oligomer polyamide 650, triethylenetetramine, ethylenediamine, diethylaminopropylamine, triethylenetetramine, phenalkamine and phenolic resin NL curing agent.
15. The expansion material according to claim 14, wherein The curing agent is oligomer polyamide 650.
16. The expansion material according to claim 1, wherein The thickness of the adhesive coating is 50-80 μm.
17. The expansion material according to claim 1, wherein The curing time of the adhesive layer is T1, and the time for the expanded core to transform into the expanded state core is T2, wherein T2 <T1。 18. The expansion material according to claim 17, wherein T1-T2=1-6h.
19. The expansion material according to claim 1, wherein The isolation layer is hydroxypropyl methylcellulose ether.
20. The expansion material according to claim 1, wherein The thickness of the isolation layer is 100-200 μm.
21. The expansion material according to claim 1, wherein The ratio of the thickness of the isolation layer to the thickness of the adhesive layer is 1:0.2-1.
2.
22. The expansion material according to claim 21, wherein The ratio of the thickness of the isolation layer to the thickness of the adhesive layer is 1:0.3-0.
8.
23. A method for preparing the expansion material according to claim 1, characterized in that: The method comprises the following steps: (1) crushing and screening the expanded raw material to obtain an expanded kernel; (2) mixing the components in the adhesive coating composition with a solvent to obtain a coating material; (3) applying the coating material to the surface of the expanded inner core to obtain a semi-finished material; (4) The semi-finished material is coated with an insulating material to obtain an expanded material.
24. The preparation method according to claim 23, wherein: The viscosity of the coating material is 100-500 mPa·S; The amount of the coating material is such that the thickness of the adhesive layer in the expansion material is 30-100 μm; The amount of the isolation material is such that the thickness of the isolation layer in the expansion material is 50-300 μm.
25. The preparation method according to claim 24, wherein: The viscosity of the coating material is 200-300 mPa·S; The amount of the coating material is such that the thickness of the adhesive coating layer in the expansion material is 50-80 μm; The amount of the isolation material used is such that the thickness of the isolation layer in the expansion material is 100-200 μm.
26. The preparation method according to claim 23, wherein The solvent is selected from any one of ethanol, ethylene glycol monobutyl ether, ethyl acetate, tetrahydrofuran, chloroform and acetone.
27. The preparation method according to claim 26, wherein: The solvent is ethanol.
28. The preparation method according to claim 23, wherein: The coating time is 1-30 minutes.
29. The preparation method according to claim 28, wherein The coating time is 5-10 minutes.
30. The preparation method according to claim 23, wherein: The coating time is 1-30 min.
31. The preparation method according to claim 30, wherein: The coating time is 5-10 minutes.
32. Use of the expansion material according to any one of claims 1 to 22 or the expansion material obtained by the method according to any one of claims 23 to 31 in the field of oil and gas extraction.
Citation Information
Patent Citations
Shape memory polyurethane foam for downhole sand control filtration devices
CN102224321A
Water-control low-temperature curing resin coated sand control particle and sand control method
CN103275686A